Influence of the Thermal Conductivity and Ambient Temperature Uncertainty on the Heat Losses through the External Wall - Marcin Koniorczyk; Witold Grymin (Buildings, 2021)
Numerous parameters assumed in the calculations of the buildings’ energy demand are uncertain. Therefore, calculations should be accompanied by determination of propagation of such uncertainties in the mathematical model. In the article, the influence of uncertainty of thermal conductivity and ambient temperature has been studied by means of the generalized perturbation stochastic finite element method and compared against the Monte Carlo results, indicating good accordance. Expected value and variance of heat flux on the internal side of the wall have been investigated. The perturbation stochastic finite element method is much more efficient than the Monte Carlo method for the analysed problem. The largest variance of temperature is noted in the node between the constructive layer and insulation.